Essays on the information role of credit default swaps - CHENG, Hao (Institutional Knowledge at Singapore Management University, 2018)
Chapter 1: Credit Default Swaps Pricing Errors and Related Stock Returns This article investigates the impacts of Credit Default Swaps (CDS) pricing errors on related stock returns. Using a parsimonious CDS valuation model, which produces an above average adjusted R2 of 90%, I find that its pricing errors significantly predict cross-section stock returns. Further investigation reveals that the cross-market return predictability channels via Merton (1974)'s structural prediction and primary dealers' capital risk. This paper provides a novel view of the complex interactions of capital markets and offers insights on the relative market efficiencies. Chapter 2: CDS Markets Informativeness and Related Hard-to-Value Stock Returns This research investigates the conundrum whether the Credit Default Swaps (CDS) market is informed relative to the equity market. To do this, we examine the impact of CDS price changes on stock returns calculated by transaction prices in various trading intervals within daily close-to-close. We find that stock returns overreact to credit news during trading hours and partially reverse after the market closes. The predictive effect of CDS news concentrates on ``hard-to-value stocks'' with high credit spreads. The reversal happens mainly because overconfident investors over-bet on credit news. Limit-to-arbitrage such as stock illiquidity and short-sale constraint cannot fully explain the predictive results. Overall, our empirical evidence suggests that CDS informed traders step into hard-to-value stocks with high credit spread levels. Chapter 3: The Effect of CDS on Earnings Quality: The Role of CDS Information This paper investigates whether the initiation of trading in credit default swaps (CDSs) on a borrowing firm's outstanding debt is associated with the decline in that firm's earnings quality. Using a differences-in-differences approach, we find that after CDS trade initiation, there is a significant reduction in intentional earnings manipulation of the underlying borrowing firms. The reduction of earnings management activities is channeled through trade credit exposures and corporate cash holdings. Further, we show that CDS prices convey distress risk information of firms with poor earnings quality and help to improve their risk fundamentals through conservative liquidity management strategy such as holding more cash, enhancing future operating cash flow, and increasing net working capital. Overall, our evidence suggests that an external monitoring role provided by CDS markets can reduce earnings management activities and mitigate the information asymmetry between corporate insiders and outsiders.